Corrosion challenges towards a sustainable society. Issue 11 (7th July 2022) - Bender, Roman; Féron, Damien; Mills, Douglas; Ritter, Stefan; Bäßler, Ralph; Bettge, Dirk; De Graeve, Iris; Dugstad, Arne; Grassini, Sabrina; Hack, Theo; Halama, Maros; Han, En‐Hou; et al.
Abstract: A global transition towards more sustainable, affordable and reliable energy systems is being stimulated by the Paris Agreement and the United Nation's 2030 Agenda for Sustainable Development. This poses a challenge for the corrosion industry, as building climate‐resilient energy systems and infrastructures brings with it a long‐term direction, so as a result the long‐term behaviour of structural materials (mainly metals and alloys) becomes a major prospect. With this in mind "Corrosion Challenges Towards a Sustainable Society" presents a series of cases showing the importance of corrosion protection of metals and alloys in the development of energy production to further understand the science of corrosion, and bring the need for research and the consequences of corrosion into public and political focus. This includes emphasis on the limitation of greenhouse gas emissions, on the lifetime of infrastructures, implants, cultural heritage artefacts, and a variety of other topics. Abstract : Credit photo: Yuvanoé / CEA The current WCO and EFC white paper aims to reveal the importance of corrosion protection in the development of a sustainable society. It gives guidance to governments, industries, academia and the general public to develop appropriate corrosion protection and mitigation strategies, as well as to allocate sufficient resources to achieve best engineering practices. Benefits include increasing safety and reliability, maximised asset life, environmental protection and economic long‐term operation.